Awareness, access, and adoption of natriuretic peptides for diagnosis of heart failure - Antoni Bayes‐Genis; Mark C. Petrie; Brenda Moura; Ovidiu Chioncel; Maurizio Volterrani; Marianna Adamo; Amina Rakisheva; Gianluigi Savarese; Carlo Gabriele Tocchetti; Marco Metra; Giuseppe Rosano (ESC Heart Failure)
Abstract Aims This survey investigates natriuretic peptide (NP) testing in community and hospital settings, assessing awareness, accessibility, and utilization. Methods and results This investigator‐initiated survey, conceived within the HFA of the European Society of Cardiology, comprised 14 questions. It underwent validation and pilot testing to ensure question readability and online system functionality. The survey was accessible for 87 days, from 5 April 2023 to 1 July 2023 via a web platform. There were 751 healthcare professionals across 99 countries who responded. Of them, 92.5% had access to NPs testing in hospital whereas 34.3% had no access to NTproBNP in community settings. Access to point of care NP testing was uncommon (9.6%). Public insurance fully covered NPs testing in 31.0% of cases, with private insurance providing coverage in 37.9%. The majority (84.0%) of participants believed that the medical evidence supporting NPs testing was strong, and 54.7% considered it cost‐effective. Also, 35.8% found access, awareness, and adoption to be in favour of NPs testing both in hospital and community settings. Strategies to optimize NP testing involved regular guideline updates (57.9%), prioritizing NPs testing for dyspnoea assessment (36.4%), and introducing clinician feedback mechanisms (21.2%). Notably, 40% lacked a community‐based HF diagnostic pathway for referring high‐NP patients for echocardiography and cardiology evaluation. Conclusions This survey reveals NP awareness, access, and adoption across several countries. Highlighting the importance of community‐based early heart failure diagnosis and optimizing HF diagnostic pathways remains a crucial, unmet opportunity to improve patient outcomes.